After 50 Years: The Promised Land is Still Too Far! 1961 - 2011 - John, Ibrahim Werrema (Book collections on Project MUSE., 2012)
The late Julius Kambarage Nyerere was nicknamed "Musa" (Moses) during the later, post-independence years for leading his people from slavery and guiding them toward a free land of prosperity - the Promised Land. The Tanzanian odyssey chronicled in this book, which first appeared ten years ago as Tanzanians to the Promised Land, has been updated with new research. The author - also an engineer and a journalist - offers a discussion of the journey and both sides of the contributions - successes and failures - made by former presidents and their systems of administration: the late Mwalimu Julius K. Nyerere, Alhajj Ali H. Mwinyi, and Mr. Benjamin W. Mkapa. Tanzanians' hopes and expectations of the incumbent president, H.E. Mr. Jakaya Mrisho Kikwete, are also discussed. It is not intended as a political campaign of any kind, for any party or any individual. As a brief, yet comprehensive guide to the understanding of the nation's political and economic history, it puts forward suggestions concerning important areas of the country's economic development. Nyerere unfortunately didn't live to see his people arrive at the hoped-for destination, and I.J. Werrema's original inspiration to write, at forty years of independence, is sustained because after fifty years The Promised Land is still too far.